RELATIONSHIP BETWEEN BMI, SOCIOECONOMIC STATUS, EXERCISE PARTICIPATION AND HABITUAL PHYSICAL ACTIVITY LEVEL OF FATHERS, MOTHERS AND THEIR CHILDREN (Fiep Bulletin - online, 2015)
The purpose of this study is to establish the relationship between BMI, socioeconomic status, regular exercise practice and daily physical activity level of children and their parents from private schools of Curitiba-PR. The sample was composed of 45 subjects (15 eight-year-old school children, 15 fathers and 15 mothers). This sample was divided in two groups: sedentary children and their parents (n=24) and active children and their parents (n=21). At first, all subjects' body mass and stature were assessed, and then the BMI was calculated. A questionnaire was used to assess the socioeconomic status, and the regular exercise practice and habitual physical activity level was determined by using, from all subjects (fathers, mothers and children), a three-day diary (BOUCHARD et al., 1983). Group comparisons were made by one-way ANOVA´s and Pearson moment product was used to verify the relationship among all variables (P
Keywords: physical activity level; socioeconomic status; parents and children.